Tick fauna in grasslands on Mt. Aso and the possibility of the tick reduction to cattle by the essential oil - Shibuya, Hikaru; Tamagawa, Yoshiki; Murata, Kouhei; Tanapoon, Moungthipmalai; Puwanard, Cheepchanok; Soonwera, Mayura (My University, 2025)
The objectives of this study were to evaluate the tick fauna in the Aso region and the repellent effects and acaricidal activity of three plant–derived essential oils against ticks. It was revealed that the most dominant species of tick in the region was Haemaphysalis longicornis, with large annual fluctuations in the number of juvenile stages. The essential oils also showed significant repellent effects against H. longicornis and were highly toxic to this species. These results suggest that spraying essential oils on cattle in spring and autumn, when juvenile stages emerge, may be useful in controlling this species by disrupting infestation.
Keywords: Asian longhorned tick; Deet; pasturage; phytochemicals; repellent; volatile oil; zoonosis